Welfare Payments and Crime - Foley, C. Fritz (The Review of Economics and Statistics, 2011)
Abstract Analysis of daily reported incidents of major crimes in twelve U.S. cities reveals an increase in crime over the course of monthly welfare payment cycles. This increase reflects an increase in crimes that are likely to have a direct financial motivation as opposed to other kinds of crime. Temporal patterns in crime are observed in jurisdictions in which disbursements are focused at the beginning of monthly welfare payment cycles and not in jurisdictions in which disbursements are relatively more staggered. These findings indicate that welfare beneficiaries consume welfare-related income quickly and then attempt to supplement it with criminal income.